2004
DOI: 10.1021/jp0402380
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Thiol-Terminated Surfaces Using Aromatic Self-Assembled Monolayers

Abstract: Self-assembled monolayers (SAMs) formed from [1,1‘-biphenyl]-4,4‘-dimethanethiol (BPDMT) and [1,1‘;4‘,1‘ ‘-terphenyl]-4,4‘ ‘-dimethanethiol (TPDMT) on Au were characterized by X-ray photoelectron spectroscopy (XPS), high-resolution XPS, infrared reflection absorption spectroscopy, near-edge X-ray absorption fine structure spectroscopy, and water contact angle measurements. The results of all experimental techniques suggest the formation of densely packed and highly oriented SAMs for both BPDMT and TPDMT, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
139
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(153 citation statements)
references
References 46 publications
13
139
0
1
Order By: Relevance
“…At first sight, these results are perhaps surprising since the complexes with two alkyl thiolate chains are expected to possess a better geometry and a stronger chelating effect leading to the formation of more stable adsorbed layers. However, such chelating effect is only observed in the complexes with shorter anchoring chains (comparing the surface coverage of bpy 2 RubpyC 4 SH with bpy 2 Rubpy (C 4 SH) 2 ) and not in the two complexes with the longer chains. Also, longer anchoring chains only seem to facilitate higher surface coverage in complexes with only one anchoring group, as evidenced by comparing the surface coverage data of bpy 2 RubpyC 7 SH and bpy 2 RubpyC 4 SH.…”
Section: Electrochemical Characterization Of the Complexes In Solutiomentioning
confidence: 95%
See 3 more Smart Citations
“…At first sight, these results are perhaps surprising since the complexes with two alkyl thiolate chains are expected to possess a better geometry and a stronger chelating effect leading to the formation of more stable adsorbed layers. However, such chelating effect is only observed in the complexes with shorter anchoring chains (comparing the surface coverage of bpy 2 RubpyC 4 SH with bpy 2 Rubpy (C 4 SH) 2 ) and not in the two complexes with the longer chains. Also, longer anchoring chains only seem to facilitate higher surface coverage in complexes with only one anchoring group, as evidenced by comparing the surface coverage data of bpy 2 RubpyC 7 SH and bpy 2 RubpyC 4 SH.…”
Section: Electrochemical Characterization Of the Complexes In Solutiomentioning
confidence: 95%
“…Also, longer anchoring chains only seem to facilitate higher surface coverage in complexes with only one anchoring group, as evidenced by comparing the surface coverage data of bpy 2 RubpyC 7 SH and bpy 2 RubpyC 4 SH. As on platinum surfaces, bpy 2 Rubpy(C 4 SH) 2 showed the highest coverage on ITO, 11% (based on an estimated area of 100 Å 2 /molecule), while for the other complexes, only around 1.5-3% of the surface was covered by the adsorbate. These results, combined with the surface coverage on platinum, showed that the optimum number of carbon atoms spacing the ruthenium centre from the sulfur atom or the optimum number of tails are parameters which are difficult to tune.…”
Section: Electrochemical Characterization Of the Complexes In Solutiomentioning
confidence: 97%
See 2 more Smart Citations
“…For these methods no precise positioning of the components is attainable. In order to move from disordered solid samples to organized monolayers, it is necessary to assemble the molecules, via covalent [1,2,3,4] or non-covalent interactions [5][6][7][8][9][10][11][12] on a substrate and to study their properties at this interface. Amongst the responsive molecules, those addressable with light and able to give a strong emission signal are very appealing since any type of surface can be used and no wiring is required for their activation [13,14].…”
Section: Introductionmentioning
confidence: 99%